The Effect of Semangit Tempeh Cookies on MUAC, Hb, and Serum Ferritin in Pregnant Women with CED - Kusumawaty, Nila; Sulaeman, Ahmad; Marliyati, Sri Anna; Laily, Noer; Fitriyah, Holif (Jurnal Gizi dan Pangan, 2023)
This study aimed to analyze the effect of semangit tempeh cookies on Mid-Upper Arm Circumference (MUAC), Hemoglobin (Hb), and Serum Ferritin (SF) of pregnant women with Chronic Energy Deficiency (CED) in Lebak, Banten. The study included 47 pregnant women with MUAC<23.5 cm who were divided into Control Group (CG) (n=22) and Intervention Group (TSG) (n=25). The mean increase in MUAC in the intervention group was 0.72±0.97 cm, while that in the control group was 0.75±1.23 cm (p>0.05), and there was an increase in hemoglobin levels of 0.84 mg/dL in the control group and 0.18 mg in the intervention group. The level of adherence to consumption of semangit tempeh cookies in the intervention group was lower than in the control group (p>0.05). The supplemental feeding of semangit tempeh cookies to pregnant women in intervention group did not have a significant effect on MUAC, Hb and serum ferritin compared to control group.